2017
DOI: 10.1115/1.4038175
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prosthesis Inertial Parameters on Inverse Dynamics: A Probabilistic Analysis

Abstract: Joint kinetic measurement is a fundamental tool used to quantify compensatory movement patterns in participants with transtibial amputation (TTA). Joint kinetics are calculated through inverse dynamics (ID) and depend on segment kinematics, external forces, and both segment and prosthetic inertial parameters (PIPS); yet the individual influence of PIPs on ID is unknown. The objective of this investigation was to assess the importance of parameterizing PIPs when calculating ID using a probabilistic analysis. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Sensitivity factors were calculated by correlating the individual PAO DOFs to the JRFs and muscle moment arms using Pearson product-moment correlation coefficients (r) at JRF1 and JRF2. Sensitivity factors were categorized as weak (0.2 ≤ r < 0.4), moderate (0.4 ≤ r < 0.6), or strong (0.6 ≤ r < 1.0) (Gaffney et al, 2017;Myers et al, 2015). Positive sensitivity factors indicate a reduction in JRF.…”
Section: Probabilistic Analysismentioning
confidence: 99%
“…Sensitivity factors were calculated by correlating the individual PAO DOFs to the JRFs and muscle moment arms using Pearson product-moment correlation coefficients (r) at JRF1 and JRF2. Sensitivity factors were categorized as weak (0.2 ≤ r < 0.4), moderate (0.4 ≤ r < 0.6), or strong (0.6 ≤ r < 1.0) (Gaffney et al, 2017;Myers et al, 2015). Positive sensitivity factors indicate a reduction in JRF.…”
Section: Probabilistic Analysismentioning
confidence: 99%
“…Whatever the approach used to identify the influential parameters, it seems important to analyse the evolution of the sensitivity measures or indices over the gait cycle as they may be different between the stance and swing phases or may vary with the joint amplitude, as it appears in the present study, depending on the knee flexion-extension. Some previous sensitivity analyses of a lower limb models have reported time averages [4,12,15,35,41], time integrals [9,29,43] as well as correlation coefficients [17,25,26,38] or root mean square differences [1] computed on the whole gait cycle. One study has reported partial derivatives of the output with respect to the parameters (calculated using a finite-difference approximations) at each instant of time of the gait cycle [36] and demonstrated varying influence of some parameters on the lower limb joint moments.…”
Section: Screening Methods and Sobol Sensitivity Analysismentioning
confidence: 99%
“…This number is already associated to a high numerical cost, but the converged value of the sensitivity indices S T i may not be reached: probably that a number larger 10000 should have been used, but the numerical cost would have been too high. Yet, n s = 10000 can be considered quite high in comparison to a number of samples in the range more generally used in biomechancis [1,4,17,20,22,25,26,40].…”
Section: Limitationsmentioning
confidence: 98%